Study Protocol for a Randomized Controlled Trial of Choral Singing Intervention to Prevent Cognitive Decline in At-Risk Older Adults Living in the Community - Tan, Jasmine; Tsakok, F. H. Maurine; Ow, Elisabeth K.; Lanskey, Bernard; Lim, Kian Siong Darius; Goh, Lee Gan; Tan, Chay-Hoon; Cheah, Irwin Kee-Mun; Larbi, Anis; Foo, Roger; Loh, Marie; Wong, Caroline Kai Yun; et al. (Frontiers in Aging Neuroscience, 2018)
INTRODUCTION: This study is a parallel-arm randomised controlled trial evaluating choral singing’s efficacy in preventing cognitive decline in at-risk older participants. METHODS: 360 community-dwelling, non-demented older participants are recruited for a two-year intervention. Inclusion criteria are self-reported cognitive complaints, early cognitive impairment based on neuropsychological test scores or multiple risk factors of dementia. Participants are randomised to either in weekly choral singing sessions or general health education. The primary outcome is cognitive performance, measured by a composite cognitive test score. Secondary outcomes include depressive, anxiety and neuropsychiatric symptoms; perceived stress; sleep quality and severity of dementia symptoms. Underlying mechanisms are examined using blood- and urine-based biomarkers and neuroimaging. RESULTS: Screening began in July 2016. The first group of participants (n=93) have been recruited. Intervention and control treatments are ongoing and will end in December 2019. DISCUSSION: An evidence-based singing intervention for dementia prevention holds potential for healthcare savings and societal welfare. Trial Registration: NCT02919748 , IRB Approval Number: NUS 2508